Integrating Religiosity and Work Ethics: Shaping an Ethical and Productive Work Culture in Muhammadiyah Regional Leadership - Abbas, Djamila; Fatah, Rahmat Abd (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the meaning of religiosity and love of money in shaping an ethical and productive work culture in the Muhammadiyah Regional Leadership of North Maluku during the Industrial Revolution 4.0 era. The study employed a descriptive qualitative method with a purposive sampling technique, involving thirteen Muhammadiyah leaders and administrators. Data were obtained through in-depth interviews, documentation, and open-ended forms, then validated by triangulation and interactive analysis by Miles and Huberman. The results indicate that religiosity plays a crucial role in maintaining honesty, responsibility, and professionalism as a moral control. Spiritual values are practiced through Islamic work ethics, such as trustworthiness, hard work, and a balance between professional and personal interests. On the other hand, love of money is understood ambivalently: as a positive drive to improve work ethic, but potentially harmful if uncontrolled, giving rise to pragmatic and materialistic attitudes. The integration of the two creates a work culture that is adaptive, balanced, and rooted in Islamic values. These findings confirm that the challenges of digitalization and materialism can be overcome by strengthening religiosity as an ethical foundation, enabling Muhammadiyah to build a modern, competitive, and civilized work culture, while prioritizing educational aspects that instill moral values and character in the next generation.